Percepcja statusu społecznego wybranych profesji oraz osobiste preferencje zawodowe studentów pedagogiki resocjalizacyjnej - Pstrąg, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
W artykule zaprezentowano wyniki badań empirycznych przeprowadzonych na grupie studentów pedagogiki resocjalizacyjnej. Dotyczą one statusu społecznego wybranych zawodów, które potencjalne wykonywać mogą w przyszłości absolwenci resocjalizacji, oraz ich preferencji zawodowych.

The article presents the results of empirical research carried out on a group of students of pedagogy of social. They relate to the social status of selected professions, that the potential to perform can in the future graduates of the rehabilitation and their preferences.
Perception of Social Status of Selected Professions and Personal Preferences Professional Students of Pedagogy of Social
Keywords: status społeczny zawodu; prestiż zawodu; preferencje zawodowe; stereotypy płci; social status of the profession; the prestige of the profession; professional preferences; gender stereotypes